Evaluasi Pembelajaran Mikro Menggunakan Model Evaluasi Cipp pada Mahasiswa Peminatan Otomotif Program Studi Pendidikan Teknik Mesin Universitas Sebelas Maret Surakarta - Abduh Arohman, Bagas Khotip; Ranto, Ranto Ranto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
This study aims to determine the results of the evaluation of the implementation of the microteaching course in the automotive specialization of the Mechanical Engineering Education Study Program, Faculty of Teacher Training and Education, based on the aspects of context, input, process, and product, as well as the overall evaluation results related to the implementation of the microteaching course in the production engineering specialization of the Mechanical Engineering Education Study Program, Faculty of Teacher Training and Education. This research is a summative evaluation study using a concurrent mixed methods approach with descriptive analysis. Data were obtained through questionnaires and interviews.The results of the study indicate that the microteaching course is an important subject and serves as a distinguishing course between teacher education and non-teacher education programs. The implementation of the microteaching course in the automotive specialization of the Mechanical Engineering Education Study Program, Faculty of Teacher Training and Education, Sebelas Maret University showed that the context aspect was categorized as good with an average score of 4.1. The input aspect was categorized as good with an average score of 3.8. The process aspect was categorized as good with an average score of 4.1. The product aspect was categorized as very good with an average score of 4.2. Overall, the implementation of the microteaching course in the production engineering specialization obtained an average score of 4.1, which falls into the good category.